On the Nature of Philosophical Knowledge - Brutianas, G. (Problemos, 1978)
The status of philosophy has till recently been given contradictory evaluations by philosophers as well as by representatives of other sciences. This is conditioned by the insufficient understanding of the peculiarities of the nature of philosophical knowledge itself. The article deals with the essential features of the nature of philosophical knowledge, i.e., the universal character of philosophy, its method and categories, the unity of the ontological, the methodological, the logical and the cognitive manifold in the system of dialectical and historical materialism as well as with the peculiarities of the criterion of truth in philosophy. It is stated in conclusion that the character of philosophical knowledge conditions vast possibilities for revealing and registering new manifestations of the peculiarities of philosophical knowledge which occur in the process of the development of science.